Formulation and Evaluation of Oral Disintegrating Tablet of Lornoxicam - Patil, Supriya C. (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT The demand of oral disintegrating tablets (ODTs) has been growing especially for geriatric and pediatric patients who have difficulties in swallowing. Lornoxicam (LX) is potent enolic acid (oxicam) derivative used in the treatment of pain resulting from inflammatory diseases of joints, osteoarthritis, surgery and sciatica. The drawback of drug is, it is practically insoluble in water and so possesses poor solubility, GI absorption and bioavailability. Hence the objective of present study is to develop oral disintegrating tablet of lornoxicam using croscormellose (CM) as super disintegrating agent and it’s kneading mixture with croscormellose. The kneading mixtures of lornoxicam were prepared with croscormellose in the weight ratios of 1:0.5, 1:1, 1:1.5. The mixture LX: CM (1:1.5) (KM) exhibiting highest dissolution rate was selected and tablets were prepared using this kneading mixture by wet granulation method. Various formulations were tried and ODT was selected which possessed optimum characteristics of disintegration time of 12 sec, hardness of 3.6 kg/cm2, friability of 0.8% and cumulative percent drug release of 99.62% in 30 minutes.